The university book in digital format. Analysis model for the circulation of academic knowledge [El libro universitario en formato digital Modelo de análisis para la circulación del conocimiento académico] (2019)
The aim of this work is to identify the new possibilities of contents and technologies of digital books as communication and informational tools of last generation within the ICT. In addition, the position and receptivity of the new formats within the university publishing world in Colombia is evidenced. The process begins with a historical-contextual analysis for the comprehension of the book and the impact of the electronic format, passing through proactive methods to approach real approximations from the characteristics of the contents, typology of devices, specifications and developments for the screen-mediated reading to the hermeneutic reading of the different sources selected for the process: Interviews and conversations with editors, producers, designers and university publishing funds. From the instruments, surveys were designed for 25 editorial groups and 9 unstructured interviews with production companies and an in-depth interview model for university librarians. It is clarified that these instruments are part of a macro research, which also reviewed the role of the electronic book in the Colombian commercial sector, accompanied by 1,500 surveys throughout the country. © Universidad de Buenos Aires.